(untitled) (Fiep Bulletin - online, 2014)
Many studies have been carried out showing that the proportion of elderly in the population will grow considerably in the coming years which will in consequence increase the demand for programmes aimed at improving their quality of life. With aging, there is a physiological, biological and psychological transformation. Regular physical activity is promising for those wishing to grow older in good health. Besides helping to increase autonomy in daily activities, a creative exercise programme can open new perspectives and re-awaken the interest of the participants, improving motivation, balance and decreasing their level of depression. With this in mind and by means of a study focused on this area, we seek to show how creativity can help in exercise for the elderly